Counseling and support services for healthcare workers in German university hospitals during the pandemic—descriptive results of a Germany-wide cross-sectional survey - Diehl, Elisabeth; Mülder, Lina Marie; Imm, Carolin; Kegel, Peter; Tolksdorf, Marian; Wiegand, Hauke Felix; Röthke, Nikolaus; Tüscher, Oliver; Lieb, Klaus; Walter, Henrik; Liebe, Susanne; Maicher, Birgit; et al. (Frontiers in Public Health, 2023)
Background Due to the SARS-CoV-2 pandemic, healthcare workers (HCWs) are experiencing tremendous levels of emotional and physical stress. Hospitals are trying to help personnel cope with work-related pressure. The aim of this study was to assess HCWs’ awareness and utilization of counseling and support services during the pandemic, HCWs’ unmet counseling and support needs, and the type and content of these services. Methods A cross-sectional online survey was conducted from January to June 2021 through the German national research organization Network University Medicine (NUM). All participating hospitals (6 in total) were asked to inform their employees about the study. Results A total of 1,495 HCWs were included in the analysis. Of these, 42.8% (n = 637) were frontline HCWs (who had contact with COVID-19 patients), 23.1% (n = 344) were second-line HCWs (who only had contact with non-COVID-19 patients) and 34.1% (n = 508) had no contact with any patients. Participating hospitals offer various counseling and support services for their staff. The percentage of respondents who were unaware of available counseling and support services ranged from 5.0 to 42.0%. Depending on the type of counseling and support services, 23.0–53.6% of the respondents indicated that counseling and support services were provided but not used, while 1.7–11.6% indicated that, despite the need for them, such services were not available. HCWs’ overall satisfaction with the provided counseling and support services and their unmet support needs differed by patient contact: Frontline HCWs reported more unmet needs for counseling and support than second-line HCWs, while second-line HCWs reported more unmet needs than HCWs without patient contact. Conclusion The results indicate that hospitals should make more efforts to inform HCWs about available counseling and support services. Hospitals could also create networks where HCWs could share information about the type and content of services and their experiences with various counseling and support services. These steps would enable hospitals to respond more quickly and effectively to the problems facing HCWs during pandemics.